Effect of Micro Silica and Polypropylene Fiber on the Properties of Cellular Lightweight Concrete Blocks: A Comparative Study - Shrestha, Suroj; Koirala, Madhav Prasad; Giri, Om Prakash; Chaulagain, Hemchandra (Journal of UTEC Engineering Management, 2025)
Cellular Lightweight Concrete (CLC) blocks are becoming increasingly popular in developing countries for several reasons, such as cost, low structural loads, easier handling, thermal insulation, speed of construction, versatility, use of local materials, environmental factors, natural disasters, and earthquake resistance. Thus, there is a seminal need for innovation to improve the performance of CLC blocks by replacing alternative raw materials in place of some of the admixtures. This study examined the effects of micro silica and polypropylene fiber (PPF) on the density and compressive strength of CLC blocks. Laboratory tests were added for micro silica, with 0%-15% of the total weight of cement, and PPF, with 0%-1.5%, as additional materials. The CLC block specimen that did not contain micro silica produced a compressive strength of 5.87 MPa. The combination of 10% micro silica produced a compressive strength of 6.82 MPa at 28 days, and we found 1% was optimum for PPF. The optimum sample contained 10% micro silica and 1% PPF with a compressive strength of 7.35 MPa, which represented a 25.21% increase over the control mix. If we exceeded these optimum amounts, we saw a reduction in compressive strength. Cellular Lightweight Concrete (CLC) is gaining popularity in developing countries for a variety of compelling reasons, including cost efficiency, reduced structural load, ease of handling and thermal insulation